District level planning: an alternative paradigm (the case of Doon Valley) - Rattan, Brij B
The basic aim of district level planning is to devise a three dimensional strategy to integrate space, time and activities in a specific well defined area to ensure optimum utilisation of resources and maximise spread effect of development. According to the author, this aim would be best achieved by preparing a plan for Planning District which may be larger than the Administrative district. Resource delineation and implementation management can be within the boundaries of administrative district. Such an approach would render comprehensive geo-physiographic and socio-economic structures in homogeneous regions, possible. He sites the example of Doon Valley in this regard. Reproduced.
Keywords: Case Study - Doon Valley; District Planning - India - Uttar Pradesh